Acinetobacter baumannii Isolation in Cerebrospinal Fluid in a Febrile Neonate - Jeong, Hoar Lim; Yeom, Jung Sook; Park, Ji Sook; Seo, Ji Hyun; Park, Eun Sil; Lim, Jae Young; Park, Chan-Hoo; Woo, Hyang Ok; Youn, Hee-Shang (The Turkish Journal of Pediatrics, 2011)
We report the isolation of multidrug-resistant Acinetobacter baumannii from the cerebrospinal fluid (CSF) of a neonate suffering from fever and irritability who was initially regarded as aseptic meningitis [CSF analysis: white blood cell (WBC), 14/mm3 (neutrophil 78%); glucose, 41 mg/dl; protein, 52 mg/dl]. The normal range of WBC counts in the CSF is fairly wide, and the symptoms of meningitis are nonspecific in this age group. This patient had several risk factors for Acinetobacter infection, including exposure to antibiotics and previous admission to a neonatal care unit; therefore, it was difficult to judge the import of the isolation of A. baumannii from the CSF in this case. With the increasing prevalence of Acinetobacter species in hospital environments, clinicians may thus be confronted with uncertainty regarding whether isolated A. baumannii is a true pathogen or a contaminant. Thus, clinicians should be familiar with the risk factors for Acinetobacter infection and clinical/laboratory findings of clinically significant CSF Acinetobacter isolates.